Fuzzy Fixed Point Theorem for Multivalued \(F\)-Contraction in \(b\)-Metric Spaces - Hunwisai, Darunee; Kumam, Poom (Communications in Mathematics and Applications, 2016)
In this work, we introduce and suggest the new concept of multivalued fuzzy \(F\)-contraction mappings in \(b\)-metric spaces. We also establish and prove the existence of an \(α\)-fuzzy fixed point theorem in $b$-metric spaces.